Criminal Liability of Parents for Traffic Accidents by Minors - Reza Reyzaldy; Dian Ekawaty Ismail; Erman I. Rahim (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The purpose of this study is to analyze the settlement of criminal cases on the liability of parents for negligence that results in minors becoming perpetrators of traffic accidents. This type of research is normative legal research with a statutory approach, a case approach and a conceptual approach. The analysis used in this study is a descriptive analysis. has not explicitly regulated the criminal liability of parents for accidents committed by children, although Civil Code Article 1367 has provided a basis for civil liability, and the new Criminal Code through Article 37 opens up opportunities for the application of the principle of vicarious liability. This study recommends the need to reconstruct the Indonesian criminal law regulation which explicitly establishes a model of parental criminal responsibility based on the principle of vicarious liability and the principle of Radbruch legal certainty, without overriding the principle of child protection in the SPPA Law.